Кордоцентрична модель прози Ганни Барвінок - Ткаченко, В. (Філологічний дискурс, 2017)
У статті здійснено літературознавчий аналіз ряду оповідань
Ганни Барвінок. Досліджується вплив кордоцентризму на формування
творчого методу, відслідковується тенденція до чуттєвості у
створенні та розв’язанні конфліктів. Творчість Ганни Барвінок
розглядається в контексті літературної доби ІІ половини ХІХ
століття. Звернуто увагу на те, які риси притаманні
кордоцентричній прозі письменниці. In the article, the literary analysis of a series of stories by Hanna Barvinok is
made. The influence of heart philosophy on the formation of the creative method is
investigated, the tendency to sensitivity in the conflict creation and resolutions is
monitored. The Hanna Barvinok’s work is considered in the context of the literary
days of the second half of the nineteenth century. The attention is paid to the features
native to the writer's heart philosophy prose.